2004
DOI: 10.1089/vim.2004.17.481
|View full text |Cite
|
Sign up to set email alerts
|

Hantaviruses: Immunology, Treatment, and Prevention

Abstract: Hantaviruses are rodent-borne bunyaviruses that are associated with two main clinical diseases in humans: hemorrhagic fever with renal syndrome and hantavirus pulmonary syndrome. It has been suggested that host-related immune mechanisms rather than direct viral cytopathology may be responsible for the principal abnormality (vascular dysfunction) in these syndromes. This review summarizes the current knowledge on hantaviral host immune responses, immune abnormalities, laboratory diagnosis, and antiviral therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
0
17

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 147 publications
2
117
0
17
Order By: Relevance
“…The most important pathogens are Hantaan (HTNV) and Seoul virus (SEOV) in the Far-East (where >90% of worldwide hantavirus infections occur), PUUV and Dobrava-Belgrade virus (DOBV) in Europe and Russia, and Sin Nombre (SNV) and Andes virus (ANDV) in the Americas [5]. The first HPS report that appeared in 1994 [3] described "a newly recognized disease" which was of paramount importance for a better understanding of an emerging viral infection in the New World, and generated an explosive surge in hantavirus research.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most important pathogens are Hantaan (HTNV) and Seoul virus (SEOV) in the Far-East (where >90% of worldwide hantavirus infections occur), PUUV and Dobrava-Belgrade virus (DOBV) in Europe and Russia, and Sin Nombre (SNV) and Andes virus (ANDV) in the Americas [5]. The first HPS report that appeared in 1994 [3] described "a newly recognized disease" which was of paramount importance for a better understanding of an emerging viral infection in the New World, and generated an explosive surge in hantavirus research.…”
mentioning
confidence: 99%
“…Moreover, hantavirus pathogenicity is not determined by the negligible viral tissue damage, but, rather, by the immunological response of the human host, the so-called "cytokine storm" [5,13]. In a series of clinical observations and in vitro experiments, Hayasaka et al and Terajima and Ennis suggested that increased capillary permeability observed in both H(C)PS and HFRS may be caused by a common immunopathological mechanism, i.e.…”
mentioning
confidence: 99%
“…Hantavirus infection is associated with two main clinical diseases in humans: Hemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome (HPS) [15].…”
Section: Discussionmentioning
confidence: 99%
“…In HFRS, the clinical course can be divided into five distinct phases and viremia is though to occur subsequent to infection of alveolar macrophage, leading to infection of kidney and lung endothelial cells.Jaundice is not very common [15].…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme immunoassays have also been developed, especially for sensitive detection of IgM antibodies [6,7].…”
Section: Introductionmentioning
confidence: 99%